Fatores de virulência e produção de biofilme de Bacteroides fragilis isolados da microbiota intestinal de cães - Reis, Ana Catarina Martins (2013)
Bacteroides fragilis is part of the fecal microbiota of animals, yet it is the most pathogenic species of the genus Bacteroides. The transformation these microrganisms commensals in pathogens agents is mainly due to its virulence factors. This microorganism has been isolated from several infections in dogs. Considering the pathogenic potential of B. fragilis and its importance in veterinary medicine, this study was designed to evaluate the virulence factors and biofilm formation of Bacteroides fragilis isolated from fecal samples from dogs. The samples used in this study were collected at the Veterinary Clinic of the State University of Ceará and processed at the Laboratory of Bacteriology of the Federal University of Ceará. Were phenotypically analyzed the virulence factors (production of hemolysins and hemagglutinins, hydrophobicity, the presence of the enzyme β-lactamase and capsule) and biofilm production of 13 strains of B. fragilis. To determine the pattern of sensitivity to clindamycin, metronidazole, chloramphenicol and penicillin was used in agar dilution technique. In vitro assays for detection of biofilms were performed by the methods Congo Red agar and Accession in microplates. All strains of B. fragilis showed capsule and produced no haemolysis. Regarding the production of hemagglutinin, 38% of the strains showed hemagglutination when used canine blood and 15% in human blood (A+). Of the strains studied, 7% had a cell surface hydrophobic. In total, 61% of the strains showed β-lactamase test positive. As regards the production of biofilm was observed by the method of strokes that 12 (92.3%) of the biofilm producers were isolated by the method and Adhesion microplates, it was found that eight (61.5%) strains were able to produce biofilm. All isolates were susceptible to metronidazole and resistant to penicillin and chloramphenicol. The rate of clindamycin resistance was 69.2%. This study showed that species B. fragilis isolated from normal canine microflora showed major virulence factors for pathogenicity, they possess the ability to form biofilms and show a high rate of resistance to clindamycin.